Individualized prediction of late‐onset dysphagia in head and neck cancer survivors. Issue 4 (7th February 2020) - Aylward, Alana; Park, Jihye; Abdelaziz, Sarah; Hunt, Jason P.; Buchmann, Luke O.; Cannon, Richard B.; Rowe, Kerry; Snyder, John; Deshmukh, Vikrant; Newman, Michael; Wan, Yuan; Fraser, Alison; et al.
Abstract: Background: Limited data exist regarding which head and head and neck cancer (HNC) survivors will suffer from long‐term dysphagia. Methods: From a population‐based cohort of 1901 Utah residents with HNC and ≥3 years follow‐up, we determined hazard ratio for dysphagia, aspiration pneumonia, or gastrostomy associated with various risk factors. We tested prediction models with combinations of factors and then assessed discrimination of our final model. Results: Cancer site in the hypopharynx, advanced tumor classification, chemoradiation, preexisting dysphagia, stroke, dementia, esophagitis, esophageal spasm, esophageal stricture, gastroesophageal reflux, thrush, or chronic obstructive pulmonary disease were associated with increased risk of long‐term dysphagia. Our final prediction tool gives personalized risk calculation for diagnosis of dysphagia, aspiration pneumonia, or gastrostomy tube placement at 5, 10, and 15 years after HNC based on 18 factors. Conclusion: We developed a clinically useful risk prediction tool to identify HNC survivors most at risk for dysphagia.